Treg cells maintain selective access to IL-2 and immune homeostasis despite substantially reduced CD25 function - Hayes, Erika T. (J Immunol, 2020)
Interleukin-2 (IL-2) is a critical regulator of immune homeostasis through its impact on both regulatory T (Treg) and effector T (Teff) cells. However, the precise role of IL-2 in the maintenance and function of Treg cells in the adult peripheral immune system remains unclear. Here, we report that neutralization of IL-2 in mice abrogated all IL-2 receptor signaling in Treg cells, but was well tolerated and only gradually impacted Treg cell function and immune homeostasis. By contrast, despite substantially reduced IL-2 sensitivity, Treg cells maintained selective IL-2 signaling and prevented immune dysregulation following treatment with the inhibitory anti-CD25 antibody PC61. Reduction of Treg cells with a depleting version of the same CD25 antibody permitted CD8(+) Teff proliferation before progressing to more widespread immune dysregulation. Thus, despite severely curtailed CD25 expression and function, Treg cells retain selective access to IL-2 that supports their anti-inflammatory functions in vivo. Antibody-mediated targeting of CD25 is being actively pursued for treatment of autoimmune disease and preventing allograft rejection, and our findings help inform therapeutic manipulation and design for optimal patient outcomes.